Effects of microRNA-136 on melanoma cell proliferation, apoptosis, and epithelial–mesenchymal transition by targetting PMEL through the Wnt signaling pathway. Issue 5 (7th September 2017) - Wang, Jiu-Jiang; Li, Zhi-Feng; Li, Xiao-Jing; Han, Zhao; Zhang, Ling; Liu, Zhi-Jun
Abstract : The study aims to evaluate the effects of miR-136 on the proliferation, apoptosis, and epithelial–mesenchymal transition (EMT) of melanoma cells by targetting premelanosome protein (PMEL) through the Wnt signaling pathway. After establishment of melanoma mouse models, melanoma (model group) and normal tissues (normal group) were collected. Immunohistochemistry was performed to determine PMEL protein concentration. Mouse melanoma cells were assigned into control, blank, negative control (NC), miR-136 mimics, miR-136 inhibitors, siRNA-PMEL, and miR-136 inhibitors + siRNA-PMEL, LiC1 (Wnt signaling pathway activator), and siRNA-PMEL+ LiCl groups. MTT, Scratch test, Transwell assay, and flow cytometry were performed to measure cell proliferation, migration, invasion, and apoptosis. Quantitative real-time PCR (qRT-PCR) and Western blotting were performed to evaluate miR-136, PMEL, β-catenin, Wnt3a, Bcl-2, Bax, Caspase, E-cadherin, and N-cadherin expressions. PMEL is highly expressed in melanoma tissues. MiR-136, Bax, Caspase, and E-cadherin expressions decreased in the model group, whereas PMEL, β-catenin, Bcl-2, Wnt3a, and N-cadherin expressions increased. Bax, Caspase, and E-cadherin expressions increased in the miR-136 mimics and siRNA-PMEL groups, whereas the expressions decreased in the miR-136 inhibitors group and LiC1 group. PMEL, β-catenin, Bcl-2, Wnt3a, and N-cadherin expressions, cell proliferation, migration, and invasion decreased, and the apoptosis rate inceased in the miR-136 mimics and siRNA-PMEL groups; whereas the tendencies were opposite to those in the miR-136 inhibitors group and LiC1 group. In the siRNA-PMEL+ LiCl group, PMEL expression decreased. These findings indicated that overexpression of miR-136 inhibits melanoma cell EMT, proliferation, migration, invasion, and promotes apoptosis by targetting PMEL through down-regulation of the Wnt signaling pathway.